Panca Waluya-Based Character Education in Civic Education: A Conceptual Model for Strengthening Students' Civic Virtue in Higher Education - Arief Firdaus; Fedro Iswandi; Salah Abobaker Almabruk Shahat; Juniawan Ramadhan (Edutech Publishing Media, 2026)
This study aims to develop a conceptual model of Panca Waluya-based character education as a Sundanese local wisdom framework for strengthening students’ civic virtue in higher education. The study is motivated by the limited integration of local cultural wisdom into character education models, which continue to be dominated by universal moral and citizenship values. Employing a qualitative library research approach, this study systematically reviewed scholarly books, journal articles, policy documents, and previous studies on character education, civic education, local wisdom, and Panca Waluya. Literature sources were selected based on their relevance, academic credibility, and contribution to discussions on character formation and civic virtue development. The collected data were analyzed using qualitative content analysis through processes of data reduction, categorization, interpretation, and synthesis of concepts. The findings indicate that the five values of Panca Waluya—cageur (well-being), bageur (kindness), bener (integrity), pinter (intellectual competence), and singer (adaptability and practical skills)—are closely aligned with the values of Pancasila and the dimensions of civic virtue. These values provide a holistic framework for developing students’ moral, intellectual, social, and civic capacities. The novelty of this study lies in the development of an integrative conceptual model that systematically connects local wisdom, civic education, and civic virtue development within the context of higher education. The proposed model positions Panca Waluya not merely as a cultural heritage but as a normative and pedagogical foundation for character education. This study contributes theoretically by enriching the discourse on culturally responsive character education and contributes practically by providing a conceptual framework that can guide curriculum development, teaching strategies, and character-building programs in higher education institutions.